Analysis of The Relationship Between Safety Culture and Safety Leadership Toward Employees’ Safety Performance Through Mediating Variable Motivation of PT. Aneka Coffee Industry - Takhsun, Maya; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study aims to analyze of the relationship between safety culture and safety leadership toward employees’ safety performance through mediating variable motivation at PT. Aneka Coffee Industry. This study employs a quantitative method with descriptive-causality research type. The population in this study were all employees of PT. Aneka Coffee Industry with total of 410 employees, while the sample was 80 employees as respondents. Data collection was carried out by distributing questionnaires to the respondent. The established data analysis used Partial Least Square Structural Equation Modeling (PLS-SEM). The results of this study showed that safety culture, safety leadership, and motivation has a significant positive effect toward safety performance. Safety culture and safety leadership has a significant positive effect toward motivation. Motivation can mediate the relationship between safety culture and safety leadership toward safety performance. Keyword: Safety Culture, Safety Leadership, Motivation, and Safety Performance.